Thrombolysis as a Treatment for Ischemic Stroke: A Case Report - Fitriyani, Fitriyani; Fadilah, Aulia Nur; Nurhardita, Fika; Atthariq, M. Naufal; Archie, Avicenna M (Medula, 2024)
Stroke is defined as a neurological deficit caused by an acute focal injury to the central nervous system, whether in the brain, retina, or spinal cord, caused by blood vessels. More than 13.7 million people suffer strokes every year, and around 70% of strokes are ischemic strokes. A 66-year-old man came to the RSAM emergency room with complaints of decreased consciousness since 3 hours of SMRS and weakness of the left limb. Physical examination revealed a Babinsky reflex (-/+), and a CT scan of the head without contrast showed thromboembolism in the right middle cerebral artery. The patient was treated with thrombolysis and medical therapy. The patient was discharged after one week of hospitalization and then scheduled for re-control at the polyclinic, and the patient's National Institute of Health Stroke Score (NIHSS) score was assessed. A total score of 5 was obtained with the interpretation of mild neurological deficits, which concluded that the patient's clinical condition had improved. Establishing diagnosis and therapy as early as possible is important for the key prognosis of ischemic stroke. Thrombolysis is the right choice as a treatment for ischemic stroke in patients who meet the inclusion criteria.